Nghiên cứu tổng hợp liothyronin từ L-tyrosin làm nguyên liệu sản xuất thuốc - Giang, Nguyễn Văn; Hà, Nguyễn Thị Ngọc; Hân, Nguyễn Văn; Huyền, Đào Nguyệt Sương; Luyện, Nguyễn Đình (Vietnam Journal of Chemistry, 2014)
Liothyronine (T3), which is used to treat hypothyroidism, myxedema coma is one of two major hormones produced by the thyroid glands of human and animal. Liothyronine monosodium had been synthesized from L-tyrosine, the product from keratin hydrolysis. T3 was obtained in 26.31 % overall yield without loss of optical activity. This process includes: Nitration of L-tyrosine to 3,5-dinitro-L-tyrosine; protection of the amino-group and the carboxyl-group; synthesis of 3,5-dinitro-4-p-methoxyphenoxy-N-acetyl-L-phenylalanin ethyl ester; reduction of the nitro-group; Diazotisation of amine-group and iodination obtains 3,5-diiodo-4-p-methoxyphenoxy-N-acetyl-L-phenylalanin ethyl ester; hydrolysis and demethylation creates 3,5-diiodo-L-thyronine; Finally, iodination of 3,5-diiodo-L-thyronine gives liothyoronine. The structure of all the compounds is determined by IR, MS and NMR spectroscopy. The quality of liothyronine monosodium was confirmed to the requirement of USP 34.